GRACE-derived ice-mass variations over Greenland by accounting for leakage effects - Baur, O.; Kuhn, Michael; Featherstone, Will (American Geophysical Union, 2009)
After more than 6 years in full operational mode, the Gravity Recovery and Climate Experiment (GRACE) satellite mission provides the opportunity to derive global secular mass changes from space-geodetic observations. Crucial for a reliable estimate of secular mass changes is the ability to correct for spectral and spatial leakage effects. Inorder to account for any leakage signal, we present and apply a four-step procedure, including a validation step based on forward gravity modeling. Most notably, our method is characterized by the separation and quantification of individual leakage sources. We test and apply our procedure to the Greenland area, which exhibits the strongest secular trend signal. On the basis of simulation studies, we demonstrate that leakage-out effects are dominant for the Greenland area, and if not accounted for, mass-change rates will be underestimated. Analyzing time-variable GRACE gravity fields covering 6 whole years (August 2002 to July 2008, inclusive), we estimate the ice-volume loss over Greenland to be -177 + 12 km3 a-1. This value is the average derived from monthly gravity field models provided by CSR, GFZ and JPL, with individual contributions of -242 + 14 km3 a-1, -194 + 24 km3 a-1 and -96 + 23 km3 a-1, respectively. We highlight that without taking leakage effects into account, mass-change amplitudes over Greenland are reduced by a factor of 2. Despite the rather large spread of the results among GRACE processing centers, our results are in better agreement with the findings from alternative GRACE analysis methods and InSAR observations.